Effect of Polymer Crystallinity in P3HT:PCBM Solar Cells on Band Gap Trap States and Apparent Recombination Order. Issue 4 (19th November 2012) - Spoltore, Donato; Oosterbaan, Wibren D.; Khelifi, Samira; Clifford, John N.; Viterisi, Aurelien; Palomares, Emilio; Burgelman, Marc; Lutsen, Laurence; Vanderzande, Dirk; Manca, Jean
Abstract The non‐geminate recombination of charge carriers in polymer‐fullerene solar cells has been modeled in the last few years with a trap‐assisted recombination model, which states that the apparent recombination order depends on the concentration of trapped charges tailing into the band gap. Higher concentrations of trapped charges lead to higher apparent recombination orders. In this work, the mass fraction f of highly crystalline nanofibrillar P3HT to the total P3HT content in P3HT:PCBM solar cells is consistently varied, controlling the temperature of a nanofibers‐P3HT casting dispersion. A systematic study of the apparent recombination order, measured with a transient photovoltage technique, as a function of f is presented. A correlation is shown between the apparent recombination order, the P3HT crystallinity, and the trap concentration in the band gap measured with an admittance spectroscopy technique.